Tamoxifen-induced hepatotoxicity and symptomatic tarlov cyst in a breast cancer survivor - coexistence or consequence? - Esmez, Omer; Deniz, Gulnihal; Esmez, Merve Yildiz (Via Medica, 2025)
Invasive breast carcinoma is among the most prevalent malignancies affecting women globally. This case presents a 47-year-old female diagnosed with invasive breast carcinoma, treated with mastectomy, chemotherapy, targeted therapy, and hormonal therapy. During follow-up, she developed hepatic dysfunction attributed to tamoxifen and subsequently experienced lower back pain due to a Tarlov cyst. The case underscores the importance of comprehensive and sustained surveillance in breast cancer survivors for the early detection and management of treatment-related complications and musculoskeletal manifestations.
Keywords: hepatic dysfunction; tarlov cyst; breast cancer introduction